(untitled) (Clinics, 2015)
OBJECTIVE:Temporal processing refers to the ability of the central auditory nervous system to encode and detect subtle changes in acoustic signals. This study aims to investigate the temporal resolution ability of individuals with mesial temporal sclerosis and to determine the sensitivity and specificity of the gaps-in-noise test in identifying this type of lesion.METHOD:This prospective study investigated differences in temporal resolution between 30 individuals with normal hearing and without neurological lesions (G1) and 16 individuals with both normal hearing and mesial temporal sclerosis (G2). Test performances were compared, and the sensitivity and specificity were calculated.RESULTS:There was no difference in gap detection thresholds between the two groups, although G1 revealed better average thresholds than G2 did. The sensitivity and specificity of the gaps-in-noise test for neurological lesions were 68% and 98%, respectively.CONCLUSIONS:Temporal resolution ability is compromised in individuals with neurological lesions caused by mesial temporal sclerosis. The gaps-in-noise test was shown to be a sensitive and specific measure of central auditory dysfunction in these patients.